ANALISIS STRUKTUR EKSTRINSIK MELALUI PENGGALIAN NILAI-NILAI PENDIDIKAN KARAKTER PADA NASKAH DRAMA “BANGUN PAGI BAHAGIA” Karya Andy Sri Wahyudi - Putri Angelina Sirait; Vina Merina Br Sianipar; Garenta Viandia Nainggolan; Martha Thidesy Gultom; Juanta Sinaga; Yensika Putri Sinurat (STKIP Subang, 2026)
This study examines the values of character education in Andy Sri Wahyudi’s play Bangun Pagi Bahagia to analyze its extrinsic structure. The study is motivated by the fact that using literary works as a learning medium is very important because they not only provide entertainment but also help develop students’ character. A descriptive qualitative research method was employed, and data collection involved document analysis and note-taking. The play Bangun Pagi Bahagia served as the primary data source, with supporting data drawn from various relevant scholarly references. Data reduction, presentation, and drawing conclusions were the necessary steps in the data analysis process. The results of the study indicate that the play script contains eighteen educational character values: religious, honest, tolerant, disciplined, hardworking, creative, independent, democratic, curious, patriotic, appreciative of achievements, friendly or communicative, fond of reading, environmentally conscious, socially conscious, and responsible. The results indicate that literary works, particularly drama scripts, can serve as effective learning tools to support the strengthening of character education and the advanceent of knowledge in the field of education.